2010
DOI: 10.1007/s11664-010-1093-8
|View full text |Cite
|
Sign up to set email alerts
|

Additive Occupancy in the Cu6Sn5-Based Intermetallic Compound Between Sn-3.5Ag Solder and Cu Studied Using a First-Principles Approach

Abstract: A Cu 6 Sn 5 -based intermetallic compound containing a certain amount of Co or Ni is commonly formed at the interface between a Cu substrate and Sn-based solder. The Co or Ni additive is often found to occupy the Cu atom sublattice in the Cu 6 Sn 5 crystal structure. In this paper, a first-principles approach based on density-functional theory is employed to explore the most favorable occupancy sites of Ni and Co dopants in the Cu 6 Sn 5 crystal structure. It is found that, for up to 27.3 at.% concentration, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…It has been observed [36] that during IMC formation, Co atoms enter the Cu sublattice of Cu 6 Sn 5 and substitutes some of the Cu atoms. Theoretical calculation revealed [37] that the presence of Co in the IMC causes a greater reduction in the heat of formation and hence makes Cu 6 Sn 5 more stable. It may be noted that similar results were obtained for nickel addition [38,39].…”
Section: Resultsmentioning
confidence: 99%
“…It has been observed [36] that during IMC formation, Co atoms enter the Cu sublattice of Cu 6 Sn 5 and substitutes some of the Cu atoms. Theoretical calculation revealed [37] that the presence of Co in the IMC causes a greater reduction in the heat of formation and hence makes Cu 6 Sn 5 more stable. It may be noted that similar results were obtained for nickel addition [38,39].…”
Section: Resultsmentioning
confidence: 99%
“…These then participate in the form of (Cu,Ni) 6 Sn5 in the bulk solder as well as at the interface. Ni atoms entered the Cu sublattice of the Cu 6 Sn 5 phase and substituted the Cu atoms to form (Cu,Ni) 6 Sn5 [46,47]. The effects of nickel, as an alloying element, on the interfacial CueSn IMC layers have been explained elsewhere [7,35,48].…”
Section: Imc Growth Kineticsmentioning
confidence: 99%
“…Crystal structure of Ni atoms is cubic as similar to crystal structure of Cu atoms. Therefore, Ni atoms substitute Cu atoms in Cu 6 Sn 5 and create (Cu, Ni) 6 Sn 5 at the interfaces and in the solder bulk [31]. Gao et al have shown, based on thermodynamic calculation, that (Cu, Ni) 6 Sn 5 is more stable than Cu 6 Sn 5 [32] .…”
Section: Discussionmentioning
confidence: 99%